Influence of four retail food service cooling methods on the behavior of Clostridium perfringens ATCC 10388 in turkey roasts following heating to an internal temperature of 74[degrees]C. - Olds, D.A.; Mendonca, A.F.; Sneed, J.; Bisha, B. (My University, 2008)
The influence of four food service cooling methods (CM) on growth of Clostridium perfringens ATCC 10388 in cooked turkey roasts was evaluated. Raw whole turkey roasts were inoculated with C. perfringens spores (~4.23 log CFU per roast), vacuum packaged, and heated to an internal temperature of 74[degrees]C. The cooked roasts were cooled as follows: whole roast cut into four quarters and held at 4[degrees]C (CM1); whole roast held in a blast chiller (CM2); whole roast loosely wrapped and held at 4[degrees]C (CM3); and whole roasts (three per bag) held at 4[degrees]C (CM4). The roasts were analyzed for C. perfringens using Shahidi-Ferguson perfringens agar and anaerobic incubation (37[degrees]C, 24 h). None of the cooling methods met the amended 2001 U.S. Food and Drug Administration Food Code guidelines for safe cooling of potentially hazardous foods. Times taken for roasts to cool from 57 to 21[degrees]C using CM1, CM2, CM3, and CM4 were 2.27, 3.11, 6.22, and 8.71 h, respectively. Times taken for roasts (218C) to reach 5[degrees]C ranged from 6.33 (CM1) to 19.45 h (CM4). Based on initial numbers of C. perfringens, no growth occurred in roasts cooled by CM1 or CM2, whereas numbers increased by 1.5 and 4.0 log in whole roasts cooled via CM3 and CM4, respectively. These findings indicate that certain food service cooling methods for whole cooked turkey roasts may result in proliferation of C. perfringens and increase the risk of foodborne illness by this pathogen.
Keywords: Cooling; Clostridium perfringens; Food service; Turkey roasts; Heating